Use of statins in cancer patients following acute myocardial infarction and its impact on long-term clinical outcomes. (3rd October 2022) - Stepien, K; Nowak, K; Kachnic, N; Horosin, G; Walczak, P; Nessler, J; Zalewski, J
Abstract: Background: Statin use and its impact on long-term clinical outcomes in cancer patients following acute myocardial infarction (MI) remains insufficiently elucidated. Purpose: We sought to analyze the prevalence of statins use in MI patients with cancer hospitalized in a tertiary cardio-oncology center and its influence on long-term mortality. Methods: Of the 1, 011 consecutive acute MI patients hospitalized between 2012 and 2017, cancer was found in 134 (13.3%) subjects including newly diagnosed cancer in 24 of them. All patients underwent coronary angiography. Within a median follow-up of 69.2 (37.8–79.9) months, a mortality rate, and its determinants were analyzed. Results: Compared with non-cancer population, MI patients with cancer were older (73 [66–79] versus 68 [60–78] years, P<0.001), had lower hemoglobin level (12.8 [11.2–14.0] vs 13.8 [12.8–15.0], P<0.001), lower total cholesterol (4.1 [3.4–4.8] vs 4.4 [3.6–5.3], P=0.006) and lower HDL cholesterol (1.1 [0.9–1.4] vs 1.2 [1.0–1.6], P<0.001), without significant differences in LDL cholesterol (2.5 [1.9–3.1] vs 2.6 [1.7–3.4], P=0.70). Statins were prescribed less frequently in MI patients with cancer as compared with non-cancer MI population (80.5% versus 92.1%, P<0.001). Atorvastatin was the most frequent statin in both cancer and non-cancer groups (68.4% versus 75.1%, P=0.13). In cancer group simvastatin was more frequently (16.7% versus 5.9%, P<0.001) while rosuvastatin was less frequently (8.8% versus 18.9%, P=0.007) prescribed than in non-cancer patients. The independent determinants of no use of statins were anemia (hazard ratio [HR] 2.3, 95% confidence interval [95% CI] 1.3–4.2, P=0.006), no coronary artery stenosis >50% (HR 5.0, 95% CI 2.5–10.1, P<0.001) and cancer (HR 1.9, 95% CI 1.01–3.7, P=0.049) but not LDL cholesterol. The mortality rates were significantly higher in MI patients not treated with statins, both in non-cancer population (29.5%/year versus 6.7%/year, P<0.001) as well as in cancer group (53.9%/year versus 24.9%/year, P<0.05) as compared to those treated with statins (Figure 1). No statin use (HR 2.3, 95% CI 1.8–3.0, P<0.001), an active cancer (HR 2.3, 95% CI 1.8–3.0, P<0.001), patient's age (HR 2.3, 95% CI 1.8–2.9, P<0.001, per year) and anemia (HR 1.7, 95% CI 1.4–2.1, P<0.001) independently increased long-term mortality while no coronary artery stenosis >50% (HR 0.65, 95% CI 0.44–0.96, P=0.03) and better left ventricular ejection fraction (HR 0.97, 95% CI 0.96–0.98, P<0.001, per 1%) improved long-term survival. Conclusions: An active cancer, anemia and lack of significant coronary lesions were associated with no use of statins in patients following MI. By multivariable approach both no statins use in MI patients independently on an active malignancy were associated with unfavorable long-term outcomes. Funding Acknowledgement: Type of funding sources: None.